Student engagement with an academic support center during Covid-19 - Aucutt, Daniel William (Kansas State University, 2021)
The challenge to improve academic achievement for community college students has generated concern for decades, with renewed emphasis during the Coronavirus Pandemic of 2020-2021, known as Covid-19 (Roueche, 1968; West & Fabre, 2021). National and local initiatives for student success have been launched with mixed results from a broad coalition of champions (Smith, Baldwin, & Schmidt, 2015). The challenge of succeeding in higher education for many students suggests that a corresponding demand for academic support services would exist, but that has not been the universal student response at every institution (Friedlander, 1980; Hendriksen, Yang, Love, & Hall, 2005). Research has demonstrated the efficacy of academic support services for students when used, dispelling most doubts about their utility (Center for Community College Student Engagement, CCCSE, 2012; Kostecki & Bers, 2008). This quantitative study is about factors that relate to student engagement with an academic support center during Covid-19. That support center is the Tutoring and Academic Skills Center (TASC) at College of the Desert (COD) in Palm Desert, California.
Keywords: Academic achievement; Support services; Student success; Student engagement